Endoscopic Foraminotomy in Spinal Epidural Lipomatosis, Case Report - Quillo-Olvera, Diego; Kim, Jin Sung; Quillo-Olvera, Javier; Quillo-Resendiz, Javier (International Journal of Innovative Research in Medical Science, 2019)
A 69-year-old woman with a history of hypertension and Cushing's syndrome, Her symptoms onset a year ago with pain in both legs treated with analgesics, but continued with right L4-L5 radiculopathy, she underwent treatment with endoscopy lumbar transforaminal, relieving his discomfort in the right leg, indicating on the visual analog scale (VAS) a score of 2/10. Four months later she started with pain in the left leg pointing to VAS of 7/10 in the disposition of the roots of L4-L5. Magnetic resonance imaging (MRI) of lumbar spine in sagittal and axial sequence weighted in T1 and T2 showed an excess of epidural fat and compression of the dural sac from L1 to S1. After the clinical-radiological assessment, the patient was treated with a left L4-L5 endoscopic foraminotomy in which adipose tissue was obtained and a decompression of the neural structures was achieved, the pain and weakness of the leg improved, indicated a VAS of 2/10 and the MacNab criteria scale for clinical graduation reported as good. We present a case of spinal epidural lipomatosis caused by Cushing's syndrome in a patient who underwent a lumbar endoscopic foraminotomy for radicular pain in a hospital in Korea.